The Dimensional Structure of the Wisconsin Schizotypy Scales: Factor Identification and Construct Validity - Kwapil, Thomas R. (Oxford University Press, 2008)
The present study examined the factor structure underlying the Wisconsin Schizotypy Scales and the validity of these dimensions. Confirmatory factor analysis with 6137 nonclinical young adults supported a 2-factor model with positive and negative schizotypy dimensions. As predicted, the schizotypy dimensions were differentially related to psychopathology, personality, and social impairment. Both dimensions were related to schizotypal and paranoid symptoms. Positive schizotypy was uniquely related to psychotic-like experiences, substance abuse, mood disorders, and mental health treatment, whereas negative schizotypy was associated with negative and schizoid symptoms. Both dimensions were associated with poorer overall and social functioning, but negative schizotypy was associated with decreased likelihood of intimate relationships. The findings support the construct validity of a multidimensional model of schizotypy and the use of psychometric inventories to assess these dimensions.